Evolution of Allan Barr’s translation style in Yu Hua's English translation works - Li, Yajie (2024)
Exploring Allan Barr's style and its evolution is crucial due to its unique and representative significance among sinologists and translators of contemporary Chinese literature. Barr's focused translation of Yu Hua's works and his ongoing interaction with the author make his translations key to understanding the fluidity of a translator's style. However, the unclear scope of translator style research, limitations in current corpus-based models, and challenges in selecting and analyzing stylistic markers necessitate further exploration of the definition, methodology, and theories related to translator style. This study aimed to (i) identify Barr's translation style by comparing the data of stylistic markers in the parallel corpus of his translation with the comparable corpora; (ii) analyse the changes in Barr's stylistic features by comparing each of his translation diachronically; (iii) evaluate the compatibility of the findings gained from the corpus-based analysis of the seven stylistic markers, namely STTR, average sentence length, ratio between English words and Chinese characters, italics, speech presentation, position of the reporting clause, and speech-act report verbs; and (iv) explain the social and cognitive factors shaping and developing Barr's translation style. This study used mixed methods to build a parallel corpus of Barr's four English translations of Yu Hua's works, alongside a comparable corpus of Andrew Jones' translations of two of Yu Hua's works, highlighting Barr’s unique stylistic choices. A diachronic analysis of Barr's translations was conducted to examine the evolution of his style. Barr's style was described using both statistical parameters and case studies for a broad perspective, while qualitative analysis categorized italicized sections and pragmatic stylistic markers. Numerical and case analyses revealed Barr's stylistic tendencies in each category, showing his efforts to clarify the target text and balance fidelity to the source text with adherence to target language norms. Insights from an interview with Barr and other extra-textual data provided a social and cognitive understanding of his stylistic development. The findings show Barr's dedication to maintaining fidelity to the source text while prioritizing readability and clarity in the target text. His second translation demonstrated more interpretive elements, reflecting nuanced decisions. Barr's early translations displayed creativity and confidence, with later works showing a more flexible and moderate approach. Although results varied across the seven stylistic markers, they collectively highlighted Barr's distinct and evolving style, confirming the revised models' effectiveness in capturing stylistic changes. The analysis also revealed that Barr's consistent style was influenced by his professional background and research interests, while his evolving style was shaped by his growing stylistic awareness, ongoing communication with Yu Hua, and interpretaion of the the source texts and, target readers. The study recommends using revised models to explore the consistent and evolving styles of translators over time, aiding researchers in selecting appropriate stylistic markers for studying translator style. Additionally, this research provides empirical data on Barr and Yu Hua's styles, laying the groundwork for future corpus-based stylistic research and translation studies on contemporary Chinese literature. Researchers are encouraged to continue examining translators' evolving styles and to engage in critical reflections on style.